Case report: Retroperitoneal solid pseudopapillary neoplasm associated with multiple hepatic metastases - Chen, Lin; Yuan, Mengchen; Wang, Meng; Luo, Chenglong; Gao, Mengyu; Huang, Qingbo; Li, Zhenqian; Zhou, Zhigang (Frontiers in Oncology, 2024)
Solid pseudopapillary neoplasm (SPN) is a rare tumor mostly occurring in the pancreas. They are lowgrade malignant tumors of the exocrine pancreas that occasionally metastasize, usually to the liver or peritoneum. Additionally, multiple metastases of extrapancreatic SPN to the liver are extremely rare and have been reported before. This study presents a case of a 13-year-old male with retroperitoneal SPN and multiple hepatic metastases. The patient presented with abdominal trauma and underwent enhanced CT, which revealed upper pancreatic occupancy and three hypodense foci in the right lobe of the liver. Moreover, increased spleen size was noted. The patient's serum tumor marker CA125 was increased to 39.00 U/mL (N < 35.0 U/mL) and circulating tumor cells (CTC) were elevated to 10.2 FU/3mL (N < 8.7 FU/3mL). The patient underwent retroperitoneal occupancy resection and splenectomy, followed by resection of liver metastases seven months after surgery. Furthermore, multiple liver metastases from retroperitoneal SPN were confirmed postoperatively. The patient recovered for one year without tumor recurrence. This case emphasizes the importance of evaluating serum tumor markers and medical imaging in young patients, as well as the fact that surgery appears to be the preferred treatment option for multiple metastases in SPN.